Chlorinated Carbon‐Bridged and Silicon‐Bridged Carbazole‐Based Nonfullerene Acceptors Manifest Synergistic Enhancement in Ternary Organic Solar Cell with Efficiency over 15%. Issue 10 (20th August 2020) - Chen, Tsung-Wei; Yu, Jun-Yan; Lin, You-Wei; Peng, Shih-Hao; Wu, Shang-Hsuan; Su, Yi-Jia; Karapala, Vamsi Krishna; Hong, Ling; Yao, Huifeng; Hou, Jianhui; Hsu, Chain-Shu
Abstract : Herein, two novel nonfullerene acceptors (NFAs), DTCC‐4Cl and DTSiC‐4Cl, are synthesized by end‐capping dithienocyclopentacarbazole (DTCC) and dithieno‐silolocarbazole (DTSiC) cores with chlorinated IC (2Cl‐IC) units, respectively. With the better‐known advantage of having the extraordinary σ *– π * conjugation of silole unit embedded in the DTSiC core, DTSiC‐4Cl manifests upshifted lowest unoccupied molecular orbital (LUMO), blue‐shifted absorption, and increased π – π interaction in comparison with DTCC‐4Cl. Furthermore, to elucidate the effect of bridging atoms on the photovoltaic performance, T1 is selected as the polymer donor to be blended with DTCC‐4Cl and DTSiC‐4Cl. T1:DTCC‐4Cl‐based devices exhibit a fine power conversion efficiency (PCE) of 14.43% and T1:DTSiC‐4Cl‐based devices exhibit a comparable PCE of 14.46%. Interestingly, the T1:DTSiC‐4Cl‐based devices demonstrate an additive‐free feature, which is worthy of further applications. From the perspective of constructing high‐performance ternary devices, DTCC‐4Cl is expected to possess excellent compatibility with DTSiC‐4Cl owing to its structural similarity. As anticipated, the ternary T1:DTSiC‐4Cl:DTCC‐4Cl‐based device outperforms the binary T1:DTCC‐4Cl and T1:DTSiC‐4Cl‐based devices, affording a decent PCE of 15.04% with a V OC of 0.97 V, a J SC of 20.80 mA cm −2, and an FF of 74.55% without any additive. Abstract : Molecular engineering of bridging atoms creates functional nonfullerene acceptors (NFAs) that not only afford decent photovoltaic performance but also ameliorate the fabrication process. DTSiC‐4Cl exhibits fine power conversion efficiency of 14.46% in binary bulk‐heterojunction organic solar cells (BHJ‐OSCs) and 15.04% in ternary BHJ‐OSCs without additives, manifesting great potential for both academic and industrial applications.